Awareness of patients with digestive diseases about treatment methods and choice of drugs - I. N. Banin; S. N. Cherkasov; O. E. Konovalov; V. I. Pak; A. L. Gorbunov (Сибирский научный медицинский журнал, 2025)
The key aspect of therapy is the correct prescription of medications and the selection of the treatment method. Such a choice (correct or incorrect) will depend, among other things, on the patient’s knowledge. Aim of the study was to investigate the awareness of patients with diseases of the digestive organs about treatment methods and the choice of drugs.Material and methods. The analysis was conducted in three groups of patients formed on the basis of observation and treatment technology. Group 1 and Group 2 included patients undergoing routine treatment in outpatient (n = 531) and inpatient settings (specialized gastroenterology department) (n = 822), respectively. Group 3 comprised patients admitted for inpatient treatment on an emergency basis to the Emergency Care Hospital (n = 147) due to complications of the underlying disease (digestive system disorders). Patients’ behavior patterns were identified by analyzing their responses to the author’s questionnaire. The groups were compared using nonparametric criteria: the association coefficient (Kass) and the χ2. Results and discussion. The most popular source of information for Group 1 and Group 2 about treatment methods and choice of medications was the Internet (34.3 and 37.1 per 100 respondents, respectively) unlike representatives of Group 3 (14.4 out of 100 respondents). The second most frequently used source of information among patients in the Group 1 and Group 2 was advice from relatives, friends, and acquaintances (30.0 and 35.4 per 100 respondents, respectively), and this source was most popular among Group 3 patients (47.2 out of 100 respondents). Sources with one-way communication to the information recipient (television, radio, newspapers) were used significantly less frequently across all comparison groups, with no statistically significant differences observed between them. Specialized literature was considered the most adequate source of information, which was also not very popular among patients in the compared groups. It should be noted that not only its paper version was considered as specialized literature, but also electronic literature that the patient could find on the Internet. In this case, the Internet can be considered both as a source of knowledge (blogs, news, etc.) and as a way to search for special literary sources, usually popular science. The study showed that the distribution of such sources of information as advice from others (not doctors or health workers) is quite high among Group 3 patients. Such advice can be recognized as interfering with the treatment process and, possibly, contributing a late start to the treatment process itself. Conclusions. Most patients undergoing routine treatment in outpatient (n = 531) and inpatient settings use adequate sources of information to select medications and methods, while inadequate sources of information are more popular among patients admitted for inpatient treatment on an emergency basis to the Emergency Care Hospital.